Optimal CMOS Analog Amplifier Circuit Design Using a Modified PSO for Consumer Electronic Applications - Rajalaxmi Das; Bishnu Prasad De; Sumalya Ghosh; Rajib Kar; Durbadal Mandal; Bhargav Appasani (Journal of Electrical and Computer Engineering)
CMOS analog amplifier circuits are integral components in the signal-processing stages of consumer electronics. They also find applications in advanced imaging systems, augmented reality devices, smartphone audio applications, power management circuits, etc. The differential and two-stage operational amplifier circuits must be optimally designed for next-generation consumer electronics devices, where speed and sizing are important constraints. This nonlinear constrained optimization problem can be resolved using evolutionary optimization techniques. This article proposes an efficient design technique for a CMOS differential amplifier circuit and CMOS two-stage op-amplifier. A well-known optimization problem is the particle swarm optimization (PSO). PSO is a robust optimization method but may suffer from premature convergence and slow convergence speed. The evolutionary technique used here is the modified version of the PSO, named Levy flight, power function, and Singer map utilized PSO (LPSPSO). In PSO, the Levy flight can enhance the exploration capability and improve the convergence speed. The proposed evolutionary technique reduces the individual circuits’ area and design time while satisfying the design constraint. The LPSPSO-based results are authenticated with SPICE. SPICE results demonstrate that LPSPSO is an efficient evolutionary technique than formerly reported methods in designing analog amplifiers in terms of MOS area, gain, power dissipation, etc.